2020
DOI: 10.3390/polym12122855
|View full text |Cite
|
Sign up to set email alerts
|

Defluorination of Polytetrafluoroethylene Surface by Hydrogen Plasma

Abstract: Defluorination of polytetrafluoroethylene (PTFE) surface film is a suitable technique for tailoring its surface properties. The influence of discharge parameters on the surface chemistry was investigated systematically using radio-frequency inductively coupled H2 plasma sustained in the E- and H-modes at various powers, pressures and treatment times. The surface finish was probed by X-ray photoelectron spectroscopy (XPS) and time-of-flight secondary ion mass spectrometry (ToF-SIMS). The measurements of water c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 31 publications
0
7
0
Order By: Relevance
“…[7] For this, various types of plasma discharges such as plasma-produced ion beam, [8,9] plasma jet, [10,11] capacitively coupled plasma (CCP), [12][13][14] inductively coupled plasma, [15] microwave plasma, [16] and so forth, were studied thoroughly. Different types of inert, as well as reactive gases like Ar, [9,[13][14][15] O 2 , [10,[16][17][18] Ar + O 2 , [8,19] He, [20] Air, [21] CF 4 , [22] and so forth, were introduced to physically and/or chemically modify the surface, eventually leading to the hydrophilic or superhydrophobic surface. For instance, Kolská et al [17] used Ar CCP to modify the surface property of 25-µm-thin PTFE foils and found that the surface became superhydrophilic (WCA = 4°) after a treatment time of 600 s. A similar reduction in the contact angle after plasma treatment was observed by Carbone et al [16] while using atmospheric pressure Ar plasma.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…[7] For this, various types of plasma discharges such as plasma-produced ion beam, [8,9] plasma jet, [10,11] capacitively coupled plasma (CCP), [12][13][14] inductively coupled plasma, [15] microwave plasma, [16] and so forth, were studied thoroughly. Different types of inert, as well as reactive gases like Ar, [9,[13][14][15] O 2 , [10,[16][17][18] Ar + O 2 , [8,19] He, [20] Air, [21] CF 4 , [22] and so forth, were introduced to physically and/or chemically modify the surface, eventually leading to the hydrophilic or superhydrophobic surface. For instance, Kolská et al [17] used Ar CCP to modify the surface property of 25-µm-thin PTFE foils and found that the surface became superhydrophilic (WCA = 4°) after a treatment time of 600 s. A similar reduction in the contact angle after plasma treatment was observed by Carbone et al [16] while using atmospheric pressure Ar plasma.…”
Section: Introductionmentioning
confidence: 99%
“…Even though PTFE is chemically inert, when exposed to the various gaseous plasma, apart from the morphological changes, severe chemical composition changes are also taken place on the surface. Depending upon the feed gas, several chemical changes such as defluorination, [19,20] chain scission, [21] crosslinking, [22][23][24][25] and post-plasma auto-oxidation [26] are reported by various research groups. For instance, Vesel et al [20] studied the defluorination of PTFE using hydrogen plasma and found that the F/C ratio decreased from 2.0 to 0.2.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…These peaks are assigned to C=C and C−H bonds, respectively. These elements are confirmed by the broad peak at 292.73 eV associated to the intense peak at 285.82 eV is in favor of the presence of CH groups on the surface of PTFE [27b] . The hydrogenation of alkenes takes place during the reaction between the modified surface of PTFE (−C=C−) and ethanol as a transposition of the Billups‐Birch mechanism applied to PTFE in the sodium naphthalenide based diglyme solution.…”
Section: Resultsmentioning
confidence: 79%
“…Such a combination was also suitable for the activation of fluorine-containing polymers such as Teflon [ 33 ]. The VUV photons break even the strongest bonds in the polymer surface film [ 34 ]. The dangling bonds interact with gaseous radicals and even molecules in the ground electronic state, thus resulting in surface functionalization.…”
Section: Conclusion and Recommendationsmentioning
confidence: 99%